Memahami Pluralisme Hukum di Tengah Tradisi Unifikasi Hukum: Studi atas Mekanisme Perceraian Adat - M.Misbahul Mujib (UIN Sunan Kalijaga Yogyakarta, 2014)
Indonesia as a country necessitates the unification of law. This is a problembecause Indonesia sociologically has many different tribes where until now still enforcecustomary law. The last few years the development of customary law where it issupported by national and international regulations. Legal unification allegedly as asingle approach will bring socio-political impact, because it will roughly relegate existinginception before the state made. The law of marriage is also not spared from theseproblems. One side the government enforce the law of marriage as unification productbut on the other hand he had to respect, preserve and even develop customary lawmarriage that is still widely used in the community. Divorce through the religious courtshas been applied but there are still many people who do divorce through traditionalmechanisms. The approach to this problem should be put forward to the wise attitude bynot prioritizing one and exclusion of the other. So that each can actually complementeach other and can survive simultaneously.